Online Loans at Perspective of Positive Law and Islamic Law; A Need or Just a Trend? (Open Society Conference, 2023)
Human’s need is basic things to provide on. But as the times growing up, the needs of human are growing as well and becoming more expensive, having more values and if its possible following the global trend. And to fulfill those needs,people will find the difficulties as their income would be insufficient. As the result, people start to find new ways to fulfill their needs and one of the easiest way in this digital era is by having the online loan. This article studied about the online loan at perspective of Positive Law and also Islamic Law. The study itself was using normative study with statutory approach and doctrinal approach. And the result of the study showed that the online loan at perspective of positivie law is one of the vital things to be regulated on and put their existence in the OJK or Otoritas Jasa Keuangan so people can safely doing the online loans in the protectiaon of state. As in the Islamic Law, the online loan is becoming the things that could not be done because it is prohibited and the prohibition has been stated also by the MUI.